Investigating the adsorption behavior and the relative distribution of Cd2+ sorption mechanisms on biochars by different feedstock. (August 2018) - Wang, Rong-Zhong; Huang, Dan-Lian; Liu, Yun-Guo; Zhang, Chen; Lai, Cui; Zeng, Guang-Ming; Cheng, Min; Gong, Xiao-Min; Wan, Jia; Luo, Hao
Highlights: Pig manure derived biochars (PBCs) have the best adsorption capacity for Cd 2+ . The contribution of involved Cd 2+ removal mechanism varied with feedstock. Cd 2+ -π interaction was the predominant mechanism for Cd 2+ removal on biochars. The ash content play an important role in the removal of heavy metal by PBCs. Abstract: The objective of this study was to investigate the adsorption behavior and the relative distribution of Cd 2+ sorption mechanisms on biochars by different feedstock. Bamboo biochars (BBCs), corn straw biochars (CBCs) and pig manure biochars (PBCs) were prepared at 300–700 °C. Adsorption results showed PBCs have the best adsorption capacity for Cd 2+, the extra adsorption capacity of PBCs mainly attributed to the precipitation or cation exchange, which played an important role in the removal of Cd 2+ by PBCs. The contribution of involved Cd 2+ removal mechanism varied with feedstock due to the different components and oxygen-containing functional groups. Cd 2+ -π interaction was the predominant mechanism for Cd 2+ removal on biochars and the contribution proportion significantly decreased from 82.17% to 61.83% as the ash content increased from 9.40% to 58.08%. Results from this study may suggest that the application of PBC is a feasible strategy for removing metal contaminants from aqueous solutions.